Using the completing the square method, for the equation, we have the zeros as x = √26 + 4 and x = 4 - √26
The given equation is presented as follows
[tex]7 = \mathbf{ {x}^{2} - 8x - 3}[/tex]
Which, by completing the square, gives;
[tex] {x}^{2} - 8x - 3 - 7 = 0[/tex]
[tex] {x}^{2} - 8x - 10 = 0[/tex]
[tex] {x}^{2} - 8x + {\left(\frac{8}{2} \right) }^{2} - 10 - {\left(\frac{8}{2} \right) }^{2} = 0[/tex]
[tex] \mathbf{{(x - 4)}^{2} } =26[/tex]
The zeros of the equation;
[tex]7 = {x}^{2} - 8x - 3[/tex]
are;
[tex] \underline{x = \pm \sqrt{26} + 4}[/tex]
Learn more about completing the square here:
https://brainly.com/question/10449635
#SPJ1